Formative pre-Hispanic agricultural soils in northwest Argentina - Sampietro Vattuone, Maria Marta (2011)
Our study area is from an early agricultural archaeological site named "El Tolar" (1st to 9th century AD), located in Tafí Valley (Tucumán, northwest Argentina). The objective was to identify geochemical signatures generated by the sustained agrarian use of soils. Chemical and pedological studies were made in different archaeological contexts. Physical and chemical features, such as bulk density, pH, organic and inorganic phosphorus, and available copper, manganese and iron, were taken into account. The results suggested that a buried paleosol identified was contemporary with the occupation of the site. It also showed characteristics clearly related to pre-Hispanic agrarian production. The concentrations of organic phosphorus and iron in agricultural soils probably reflect the use of fertilizers. The application of geoscience techniques allowed us to obtain important information on their behaviour and socio-economic development. This paper constitutes the first pedogeochemical approach to the study of Argentinean pre-Hispanic agricultural soils.